2021
DOI: 10.3991/ijoe.v17i13.26871
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning Application: Effect of Learning Readiness and Community Learning Toward Technology Management and Mobile Learning

Abstract: The use of mobile learning applications in current conditions and the challenges of learning in the digital era has become a necessity and cannot be avoided for efficiency and effectiveness in learning anywhere and anytime. This study aims to analyze the Effect of Learning Readiness and Community Learning Toward Technology Management and Mobile Learning. Besides that, it also looks at how effective the application of mobile learning applications is in learning. This research is quasi-experimental research. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The capacity to relate transferred information to practical consequences and student achievement is one reason for this impact. This corresponds to mobile learning, which focuses on students' newly acquired information and abilities (Merrill, 2022;Jamaris et al, 2021). Using self-produced films as a complement to practical classroom instruction also allows teachers, tutors, and supervisors to provide feedback on students' clinical performance.…”
Section: Figure 7 Discussionmentioning
confidence: 99%
“…The capacity to relate transferred information to practical consequences and student achievement is one reason for this impact. This corresponds to mobile learning, which focuses on students' newly acquired information and abilities (Merrill, 2022;Jamaris et al, 2021). Using self-produced films as a complement to practical classroom instruction also allows teachers, tutors, and supervisors to provide feedback on students' clinical performance.…”
Section: Figure 7 Discussionmentioning
confidence: 99%
“…The Cronbach alpha reliability coefficient of the measurement tool as a whole was calculated as 0.95. The measuring tool was in the range of strongly disagree' (1), 'disagree' (2), 'undecided' (3), 'agree' (4) and 'strongly agree' (5). The measurement tool was collected from the people who participated in the research in the form of an online environment with a Google survey.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…It is observed that important developments have been recorded in the mobile field with the ever-renewing and developing technology. Its main developments are the strengthening of laptop and tablet computers, the spread of pocket computers, portable media players and smartphones [5]. It is seen that wireless connection, GPRS connection, Bluetooth and infrared connection possibilities are increasingly used in order to enable mobile devices to connect online by themselves or by using them together.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a rise in the utilization of mobile technology in education [3]. Numerous studies have provided evidence of the effective utilization of mobile technology in augmenting and facilitating student learning [4]- [6]. However, it is crucial to acknowledge that mobile technology-based learning cannot completely replace traditional classroom settings or other technology-supported learning approaches [7].…”
Section: Introductionmentioning
confidence: 99%